2019
DOI: 10.7771/2157-9288.1246
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Teacher Professional Development on Implementing Engineering in Elementary Schools

Abstract: for additional information. This is an Open Access journal. This means that it uses a funding model that does not charge readers or their institutions for access. Readers may freely read, download, copy, distribute, print, search, or link to the full texts of articles. This journal is covered under the CC BY-NC-ND license.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 12 publications
(33 reference statements)
0
28
0
Order By: Relevance
“…A recent study indicated few secondary science teachers felt prepared to teach engineering principles related to defining engineering problems, developing possible solutions to technological problems, and optimizing design (Smith 2020). It is essential for teachers to incorporate openended engineering design challenges in their instruction to effectively integrate engineering with science, mathematics, and technology content (Porter et al 2019). Consequently, there is a need for professional development for science educators that will foster participants' engineering literacy.…”
Section: Science and Engineering Integrationmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study indicated few secondary science teachers felt prepared to teach engineering principles related to defining engineering problems, developing possible solutions to technological problems, and optimizing design (Smith 2020). It is essential for teachers to incorporate openended engineering design challenges in their instruction to effectively integrate engineering with science, mathematics, and technology content (Porter et al 2019). Consequently, there is a need for professional development for science educators that will foster participants' engineering literacy.…”
Section: Science and Engineering Integrationmentioning
confidence: 99%
“…These aspects include collective participation, focus on disciplinary content knowledge, active teacher learning, and coherence through an overall program of teacher learning and ongoing communication (Garet et al 2001). In the context of STEM professional development, promising programs have focused on situated engineering design experiences, using data to make evidence-based decisions, and implementing open-ended investigations to iteratively revise prototypes (Cunningham et al 2007;Porter et al 2019).…”
Section: University-based Stem Teacher Professional Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that specific training guidelines would help in achieving the expected outcomes in the process of training teachers on the job. Porter et al (2019) carried out a study at the Science Museum of Boston concerning implementing Engineering topics at ECD level.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, teachers mentioned the following challenges in terms of implementing EDP in their classrooms: (a) not having extra time to engage students in the design process, (b) limited resources and materials, (c) ways to facilitate student's varied ideas and designs, (d) ability to grade non-traditional assignments, and (e) helping students who are struggling with their design/project [5], [6]. Moreover, in the study conducted by Porter et al [7], they found that planning open-ended design challenges pertinent to the curriculum is difficult for teachers, particularly those who are inexperienced in teaching EDP. Hsu, Purzer, and Cardella [8] conducted a separate study with 192 elementary classroom teachers that suggested a need to improve teachers' familiarity with EDP.…”
Section: Introductionmentioning
confidence: 99%